A Handbook on Geohelminths - Kavana, Nicholas J. (A Handbook on Geohelminths, 2021)
Nematodes (roundworms) are non-segmented helminthes. They are bilaterally symmetry, have a complete digestive tract with oral and anal openings, they taper at both ends. They are easily distinguishable from other helminthes because of their cylindrical non-segmented bodies. Most nematodes are dioecious, the male and female reproductive organs are located in the body cavities of the separate sexes. Adult parasites cause less disturbances than those caused by the larvae of the parasites. Ascaris lumbricoides migrate into important organs, resulting to serious symptoms. Ancylostoma duodenale continuously suck up human blood resulting in anaemia. In molecular biology of parasites there are a number of techniques which are routinely used. DNA and RNA of helminths can be extracted by freeze-thawing lysis, this is because of their thick cuticles. Diagnosis of parasitic infections has usually been carried out by finding the causative agent and this is the most satisfactory method when dealing with infections in individuals. Parasitic infections present immune situation, which the host develops a normal immune response against the parasite but, this response does not result in its elimination. Helminths do not multiply within their vertebrate hosts. Most helminthes have life cycles in which larval stages larval stages migrate around the body of the host before the adults settle in their final sites.